Ultra-Rapid Freezing Preserves Morphofunctional Integrity and Fertilizing Ability of Epididymal Cat Spermatozoa - Colombo, Martina; Morselli, Maria Giorgia; Zahmel, Jennifer; Luvoni, Gaia Cecilia (Frontiers in Veterinary Science, 2022)
Vitrification and ultra-rapid freezing, which are more commonly used for oocytes and embryos, have recently been applied to spermatozoa in an attempt to make semen cryopreservation in field conditions easier compared to conventional freezing. It is well known that in case of unexpected death of rare and wild animals, preserving epididymal spermatozoa from isolated testicles represents a great chance of salvaging male germplasm for future use in assisted reproductive technologies. The aim of this study was to evaluate the morphofunctional integrity of cat epididymal spermatozoa ultra-rapid frozen in pellets or straws with two different extenders [E1 (TRIS buffer with 20% egg yolk 20 and 0.25M sucrose) or E2 (Ham’s F10 with 1% bovine serum albumin and 0.4M sucrose)] and to test whether spermatozoa preserved by the best combination were able to fertilize oocytes and produce embryos in vitro by intracytoplasmic sperm injection (ICSI) of in vitro matured cat oocytes. Results showed that E1 and E2 in straw or pellet were comparable (at warming, about 30% normal morphology, 45% intact membranes and 20% intact acrosomes), except for post-warming motility that was better maintained along time by E1 pellet (21.7±7.4% at warming and 3.6±2.9% after 6 hours). Such spermatozoa could fertilize conspecific oocytes and support embryonic development (cleavage 35.5%) as well as frozen control spermatozoa (cleavage 54.29%, p=0.22). In conclusion, cat epididymal spermatozoa better maintained their morphofunctional features after ultra-rapid freezing with E1 and could successfully produce embryos in vitro after ICSI. This underscores their usefulness as cryobanked material for fertility and biodiversity preservation purposes.